(untitled) - Nguyễn, Mạnh Cường (Hanoi, 2009)
On motivation and active participation of civil society organizations in the development of public services and consultation to assess the development policies in Vietnam.
Keywords: Civil society,Non-governmental organizations,Xã hội dân sự,Các tổ chức phi chính phủ; Vietnam,Vietnam,Việt Nam,Việt Nam